The “How” and “What” of Aesthetic Experience. Some Reflections Based on Noë’s Strange Tools. Art and Human Nature - Francesca Forlè (Rosenberg & Sellier, 2018)
Being a book on art and its nature, Strange Tools deals with aesthetic experience as a crucial object of inquiry. Indeed, it offers several interesting insights into what aesthetic experience is and how we should (or should not) account for it. However, some aspects of Noë’s analysis raise questions, both about the act and about the object of aesthetic experience itself. In this paper, I will discuss these issues highlighting a potential conflict in the author’s analysis of aesthetic experience and providing some hints about the objective correlate of such an experience.